The Anti- Inflammatory Effects of Spinacia Oleracea Leaf Extract on Carrageenan Induced Inflammation in Rats (Journal of Dhaka Medical College, 2018)
Context: Use of herbal medicine throughout the world is increasing. Plants still remaining the primary source of supply of many important drugs used in modem medicine. Spinacia Oleracea i,e spinach leaves contain more number of anti-inflammatory phytochemcicals such as carbohydratie, tanins and phenolic compounds, saponins, flavinoids and steroid. Better collagenation seen under the influence of the flavinoids, phenolic compound and saponins which is responsible for the free radical scavenging activity and are believed to be some of the most important component for wound healing and antioxident activity. Spinacia Oleracea scavenges free oxygen redicals and increases the catalase level in granulation tissue. Plants still remaining the primary source of supply of many important drugs used in modem medicine. Considering its medicinal value and availability in our country this study was undertaken to evaluate the antiinflammatory effect of the Spinacia Oleracea leaf extract in rat models.Material and Methods: The experiments were carried out on 30 (thirty) Swiss male albino rats. They were collected from the ICDDRB, Dhaka. The rats were of male weighing between 150- 200gm which were divided randomly into 5 groups each having 6 rats. Groups were labeled as group-I, group-II, group-III, group-IV and group-V. The anti inflammatory effect of Spinacia Oleracea leaf extract in experiment rat were evaluated and compared with the anti inflammatory effects of aspirin and hydrocortisone. The study was prospective experimental type and was conducted in the department of Pharmacology, Dhaka Medical College, Dhaka, from July 2011 to June 2012.Result : Administration of mathanolic extract and water extract of Spinacia Oleracea leaf at a dose of 200mg/kg body weight orally produced a significant (P